Energy consumption, wear and corrosion of PEO coatings on preanodized Al alloy: the influence of current and frequency - M. Mohedano; E. Lopez; B. Mingo; S. Moon; E. Matykina; R. Arrabal (Journal of Materials Research and Technology, 2022)
The influence of current and frequency on energy consumption of plasma electrolytic oxidation (PEO) of a commercial aluminium alloy pre-treated by conventional anodizing in sulphuric acid has been investigated. The combination of a 20-μm thick precursor anodic porous film, high current (500 mA cm−2) and frequency (400 Hz) during PEO enables up to 76% energy savings compared to direct PEO treatment (50 Hz). The time needed to achieve a uniform coating thickness was also reduced from 3350 s to 750 s, for PEO_50 and A + PEO_400, respectively. The wear and corrosion performance of the optimised coatings (400 Hz) were also improved despite the lower thickness of the coatings. Such improvement was mainly attributed to the microstructural refinement associated with high frequency processing and early transaction to the “soft-sparking” regime. The modification of the frequency has a stronger influence on the corrosion response than the presence of the anodic precursor. The best corrosion response was obtained for PEO_400 followed closely by A + PEO_400.